Current state and future of CLT construction in Finland : Interview study 2016 - Vatanen, Mikko; Sirkka, Antti; Pirttinen, Valtteri; Ahoranta, Tytti (Lapin ammattikorkeakoulu, 2017)
This interview study was conducted within the Future possibilities for CLT (FCLT) Nya möjligheter för CLT project financed by ERDF Interreg Nord. FCLT is a research project implemented by Luleå Technical University, Technical Research Institute of Sweden (SP), Centria University of Applied Sciences, Digipolis and Lapland University of Applied Sciences. The project started in September 2015 and will continue until May 2018. The main goal of the project is to promote the use of CLT and to increase the knowledge about the possibilities of CLT as a building material within the Interreg Nord area. The interview study was executed with a qualitative research approach and data was collected by means of a semi-structured interview. Case study was used as a research method and the experiences of using CLT in the Finnish construction industry were studied as cases. The study was planned to include wide variety of actors from different phases of construction projects. A total of 18 different professionals that have been involved with CLT building projects were interviewed. The aim of the interview study was to find answers to the main research question: What are the experiences of construction professionals on using CLT in building projects? Answers to more defined subsections were also expected: Differences when compared to other building systems, The effects of the material’s characteristics, Know-how and competitiveness, and Future expectations and needs for development. Based on the themes that were identified from the interview data, a strategic action plan called Build using CLT was created. The action plan has five different sections and the proposed actions were written as in the imperative mood so as to make the message clear and the use would be as simple as possible. The Build using CLT action plan consists of the following sections: Use the value of the material, Work efficiently, Be active in communications, Develop operational models and Co-operate and evolve. Based on the interview data, the most discussed topics were additionally highlighted using word clouds. Based on the results of the interviews, we can conclude that CLT has a positive image and it is seen to have a great deal of potential to serve as an ecological alternative for future sustainable construction. Wooden surfaces are seen as valuable and aesthetically impressive enablers of high-quality indoor environments. As a construction material, CLT is a relative newcomer, and the lack of references and experience are seen as its main challenges at the moment. The expected effect of executing the case study was to widen the perspective of earlier work in FCLT project regarding the knowledge-base of building with CLT. During the next phase of the project the focus will be in helping the companies in the Interreg Nord area to find new possibilities for business in using CLT. The objectives in the next phase are to create interest towards CLT and sustainable building solutions and then to help companies create preliminary value chains for CLT construction. The work towards the objectives is carried out by mapping the interested pilot companies, working together in workshops and distributing information via seminars, informative sessions and publications. The interview study aimed to determine the experiences that operators involved in various phases of construction have had with regard to CLT con-struction. The study sought to interview the selected operators as extensively as possible with regard to the various phases of the construction project. Based on the study, we can conclude that CLT has a positive image and it is seen to have a great deal of potential to serve as an ecological alternative for future sustainable construction. Wooden surfaces are regarded as valuable and aesthetically impressive enablers of high-quality indoor environments. CLT is still relative new as a construction material, and the lack of refer-ences and experience are seen as the main challenges at the moment. The “Build using CLT” collection of operating strategies was prepared based on the themes that emerged over the course of the interview study. The interview study report was prepared under the Future possibilities for CLT (FCLT) project, which is implemented as an Interreg Nord research proj-ect funded by the ERDF. The project involves the Luleå University of Tech-nology, SP Technical Research Institute of Sweden, Centria UAS, Digipolis Oy and Lapland UAS. The primary objective is to promote the diverse use of CLT and increase awareness of the possibilities provided by CLT construction in the Interreg region. The project was initiated in September 2015 and will continue until October 2018.